Road Fund, Solution for Funding Road Maintenance - Gatot Rusbintardjo (International Conference on Coastal and Delta Areas, 2015)
It can be denied that most of roads condition in Indonesia is worst. It is because maintenance works is not properly conducted because of insufficiently, unsustainably, and inconsistency on allocating budget for maintenance. Insufficient or uncertain budgetary allocations to road maintenance have resulted in road deterioration that has significantly increased production and transport costs. To avoid this problem, highway professionals advocate the establishment of dedicated road funds, managed by independent road boards made up of road user representatives. So far roads maintenance in Indonesia is financed using the government budget allocation. It is difficult to give guarantee to the sustainable road maintenance if the finance for road maintenance takes from the government budget allocation. Therefore in this paper will be introduced road fund, the road maintenance funding system widely used in some countries that road conditions can be well maintained. The conclusion isthat the road fund needs to be applied to maintenancethe road in Indonesia.Keywords: Road, deteriorate, maintenance, road fund, budget system, sustainable